메타버스를 위한 디지털 휴먼과 메타휴먼의 제작기법 분석 연구 - 오문석(Oh, Moon Seok); 한규훈(Han, Gyu Hoon); 서영호 (Seo, Young-Ho) (한국디자인리서치, 2021)
1996년 최초의 가상 인간의 등장 이후 가상 인간을 통한 다양한 시도가 이루어져 왔으나 기술적 한계로 그 영향력을 발휘하지 못하였었다. 그러나 최근 기술의 발전을 통해 가상 인간은 디지털 휴먼으로 다시 등장하게 되었다. 디지털 휴먼은 실제와 구분하기 어려울 정도로 인간의 모습, 행동과 유사한 3D 가상 인간으로 기술의 발전은 가상 인간의 제작을 용이하게 만들었고 다양한 분야에서 활용되고 있다. 그러나 다양한 활용 분야와 수요에도 불구하고 제작 과정상의 한계로 인하여 디지털 휴먼의 개발과 사용의 범위가 제한되고 있다. 이에 따라 본 연구에서는 디지털 휴먼에 대한 선행연구의 분석을 통해 디지털 휴먼을 정의하였고 제작 기법에 관한 연구를 바탕으로 현재의 기술적 한계를 극복하고 혼합현실 환경에 적용할 수 있는 발전된 형태의 디지털 휴먼으로서 메타휴먼을 제안하였다. Since the first virtual human appearance in 1996, various attempts have been made through virtual human beings, but due to technical limitations, they have not been able to exert their influence. However, with recent advances in technology, virtual humans have reemerged as digital human beings. Digital Human is a 3D virtual human being similar to human appearance and behavior that is hard to distinguish from reality, and technological advances have facilitated virtual human production and are being utilized in a variety of fields. However, despite various applications and demands, the scope of digital human development and use is limited by limitations in the manufacturing process. In this study, we defined digital human through the analysis of prior studies on digital human and based on our work on fabrication techniques, we propose meta-human as an advanced form of digital human that can overcome current technical limitations and apply to mixed-reality environments. KCI Citation Count: 0